Hähmäinen ja historiaton? Neljäs sektori ilmiönä ja käsitteenä turvallisuustoiminnan kontekstissa - Raisio, Harri; Puustinen, Alisa; Wiikinkoski, Tarja; Valtonen, Vesa; Lindell, Juha (Hallinnon tutkimuksen seura, 2023)
Obscure and rootless? Fourth sector as a phenomenon and concept in the context of safety and security work This article explores the concept and pheno menon of the fourth sector as an element of safety and security work. The article is based on interviews with 18 public authorities and NGO actors working in expert or managerial positions associated with nuclear emergencies. The article’s findings and previous literature indicate that the concept of the fourth sector remains somewhat unclear, rootless, and confusing. The use of the term differs in different contexts and different research streams remain rather separate and siloed. Nevertheless, the phenomenon itself is more selfevident: The fourth sector in safety and security work refers, in general, to spontaneous, temporary, and selforganizing actions appearing in informal, unstructured settings, on both the group and individual levels of civil society.
Keywords: fourth sector; third sector; safety and security work; fi=Sosiaali- ja terveyshallintotiede|en=Social and Health Management|